Causes and effects of war, means of production and development in Colombia - Bonilla Castillo, Victor Enrique (Seven Editora, 2023)
This text links important theories about the State, society, and development, important edges for the analysis of the social sciences, relating it to forced displacement due to war, economic interests, and the means of production in Colombia. This a topic that is important to address with authors who have contributed to the science of political economy, transcendental for the historical evolution of man. It is important, then, on the one hand, to make an introduction from the theory, as well as not to lose sight of the abstract and concrete categories in the study of displacement due to the armed conflict. As well as sustaining the general vision of the historical context in the Colombian war, without losing sight of the object of study from the dialectic: the massive and violent displacement of the peasant and worker population, due to economic interests, the hoarding of the land and natural resources. A bibliographical methodology is used, retaking the method of dialectical materialism. These advances are part of the research thesis for the doctorate in Development Studies. DOI: https://doi.org/10.56238/alookdevelopv1-006